2018
DOI: 10.1007/s00428-018-2404-3
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear loss and cytoplasmic expression of androgen receptor in penile carcinomas: role as a driver event and as a prognosis factor

Abstract: Androgen receptor (AR) is a member of the steroid and nuclear family receptor that acts as transcription factor. AR signaling plays pivotal role in the development and progression of prostate cancer. However, the role of AR in penile cancer (PeCa) is poorly explored. Our previous molecular studies unveiled frequent AR mRNA loss in PeCa, which was further predicted as a major driver alteration in this neoplasm. Herein, we assessed the AR protein expression in 59 usual PeCa tissues and 42 surrounding normal tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Non-nuclear AR expression was recently reported in canine PC [19,44]. However, in human cancers, including PC, non-nuclear AR signaling has been associated with aggressive characteristics, including epithelial-mesenchymal transition and metastasis [45,46]. AR nuclear expression is associated with hormone-dependent signaling pathways; however, AR splice variants can be found with different cellular localization, with a clinical impact on human patients [47].…”
Section: Discussionmentioning
confidence: 99%
“…Non-nuclear AR expression was recently reported in canine PC [19,44]. However, in human cancers, including PC, non-nuclear AR signaling has been associated with aggressive characteristics, including epithelial-mesenchymal transition and metastasis [45,46]. AR nuclear expression is associated with hormone-dependent signaling pathways; however, AR splice variants can be found with different cellular localization, with a clinical impact on human patients [47].…”
Section: Discussionmentioning
confidence: 99%
“…Several potentially targetable dysregulated oncogenic pathways have been described in PeCa [9,38,[72][73][74], including PI3K/Akt/mTOR, EGFR, and ERRB2, among others. Recently, clinical trials testing immunotherapy in PeCa patients have shown promising results [75].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in addition to canonical AR signaling in the nucleus, nongenomic AR signaling occurs in the cytoplasm [119]. In penile carcinomas, non-genomic AR signaling has been suggested to play a role and to correlate with poor prognosis and relate to shorter overall survival [120]. It is unknown whether the cytoplasmic AR attracts signals from the surrounding stromal cells or sympathetic nerves located in the prostate cancer tumor microenvironment.…”
Section: Receptors 251 Steroid Receptorsmentioning
confidence: 99%
“…It is unknown whether the cytoplasmic AR attracts signals from the surrounding stromal cells or sympathetic nerves located in the prostate cancer tumor microenvironment. The cytoplasmic AR binds to several proteins and activates several signaling molecules including SRC, RAS, MAPK, AKT, EGFR, and PI3K among others in prostate cancer [120][121][122]. As AR inhibitor ENZ leads to accumulation of high levels of cellular cytosolic AR, it is interesting to found out whether the high levels of cytosolic AR have any specific role in ENZ-induced NEPC transdifferentiation [123].…”
Section: Receptors 251 Steroid Receptorsmentioning
confidence: 99%